Carbon Isotopic Fractionation in Organic Matter Production Consistent With Benthic Community Composition Across a Coral Reef Flat - Koweek, David A.; Forden, Atleigh; Albright, Rebecca; Takeshita, Yuichiro; Mucciarone, David A.; Ninokawa, Aaron; Caldeira, Ken (Frontiers in Marine Science, 2019)
Carbon fluxes on coral reefs (net community production and net community calcification) aggregate the collective activity of all coral reef community members. This integrated approach provides powerful community-level insights, but is unable to resolve the finer-scale contributions of different reef functional groups to the community-scale rates. Tools are required to disaggregate the community-scale approaches and evaluate the performance of co-existing reef functional groups. Such assessments are necessary to improve forecasts of coral reef responses to global and local environmental change. We present results from a coral reef field study on One Tree Island reef in the Great Barrier Reef, off northeastern Australia, in September-October 2016 where we combined observations of total alkalinity, dissolved inorganic carbon (DIC), and the stable isotopic composition of dissolved inorganic carbon (δ13CDIC) to estimate carbon isotopic fractionation during organic matter formation. Portions of the reef with greater abundance of non-calcifying algae fractionated DIC 5‰ more (stronger preference for 12C) during organic metabolism than did portions of the reef with a greater abundance of calcifiers. These results were consistent across a wide range of assumed isotopic fractionation factors for net calcification. We attribute the observed differences in carbon isotopic fractionation to the metabolic activities of the ecological community underlying each section of the reef, rather than to environmental factors such as light availability or water temperature. The patterns in carbon isotopic fractionation were generally consistent with inferred ratios of calcification to primary production in each reef zone, giving further confidence to our inference that differences in carbon isotopic fractionation may be related to differences in the ecological community on small spatial scales.